SPECIFIC FEATURES OF THE INTRODUCTION OF INCLUSIVE EDUCATION (American Journal of Interdisciplinary Research and Development, 2024)
After the Republic of Uzbekistan gained independence, drastic changes took place in the process of economic, social, spiritual and educational development of our country. The priority policy of our state to democratize the education system and its content is to make the youth of the 21st century a well-rounded, well-educated, well-rounded person. The Law "On Education", "National Program of Personnel Training" managed to update the quality of education of the young generation from the lower level of education to the higher education system. 'lindi. CHunonchi. The future of our MotherlaIInd directly depends on the education, potential, talent and independent thinking of today's young generation. That is why the task of educating knowledgeable, broad-minded people has been raised to the level of the priority task of our state policy.